How Sexual and Gender-Based Violence Affects the Settlement Experiences Among Yazidi Refugee Women in Canada - Bhattacharyya, Pallabi; Songose, Labe; Wilkinson, Lori (Frontiers in Human Dynamics, 2021)
Gender and sexual violence is commonly used as a weapon of war throughout history. Yazidi women resettled in Canada directly from northern Iraq after the 2014 Daesh-led attacks in the Sinjar region have experienced severe human rights violations and sexual and gender-based violence. These have impacted both physical and mental health of most of these women. However, research on pre-arrival trauma and its impact on resettlement has been limited to individual psychological interventions without considering how these experiences may affect the overall settlement experience. Our paper focuses on the settlement challenges and needs of 21 Yazidi women resettled in the four Canadian cities with the largest number of Yazidi refugees. Because the resettlement of the Yazidi often happened within weeks after their release from captivity, the deficiencies within the Canadian network became more visible with this group. We argue that although the Canadian resettlement program is generous in many ways, it falls short of adequately addressing many of the trauma issues, especially sexual and gender-based violence, experienced by many refugees pre-arrival. Our analysis reveals that single-female headed families, particularly with young children, have a very difficult time navigating the resettlement system in Canada. We have identified the resettlement experience into three stages as there are time-based consequences to how trauma influences various aspects of the resettlement process. The first stage is the critical period that lasts for the first six weeks and could last for up to three months post-arrival as many women require more dedicated support of settlement providers for housing, language, and health. The second stage is referred to as the period of adjustment which is during the first year and a half, depending on the quantity of settlement services that women can access based on their mental and physical health conditions at that time. The third stage begins sometime after the first year when many women can start navigating the system on their own. Thinking of how SGBV may influence the resettlement process in stages is a good way for us to consider the additional assistance that may be needed and how the women can receive it.